Effects of climate change on the delivery of soil‐mediated ecosystem services within the primary sector in temperate ecosystems: a review and New Zealand case study. (8th June 2015) - Orwin, Kate H.; Stevenson, Bryan A.; Smaill, Simeon J.; Kirschbaum, Miko U. F.; Dickie, Ian A.; Clothier, Brent E.; Garrett, Loretta G.; van der Weerden, Tony J.; Beare, Michael H.; Curtin, Denis; de Klein, Cecile A. M.; Dodd, Michael B.; et al.
Abstract Future human well‐being under climate change depends on the ongoing delivery of food, fibre and wood from the land‐based primary sector. The ability to deliver these provisioning services depends on soil‐based ecosystem services (e.g. carbon, nutrient and water cycling and storage), yet we lack an in‐depth understanding of the likely response of soil‐based ecosystem services to climate change. We review the current knowledge on this topic for temperate ecosystems, focusing on mechanisms that are likely to underpin differences in climate change responses between four primary sector systems: cropping, intensive grazing, extensive grazing and plantation forestry. We then illustrate how our findings can be applied to assess service delivery under climate change in a specific region, using New Zealand as an example system. Differences in the climate change responses of carbon and nutrient‐related services between systems will largely be driven by whether they are reliant on externally added or internally cycled nutrients, the extent to which plant communities could influence responses, and variation in vulnerability to erosion. The ability of soils to regulate water under climate change will mostly be driven by changes in rainfall, but can be influenced by different primary sector systems' vulnerability to soil water repellency and differences in evapotranspiration rates. These changes in regulating services resulted in different potentials for increased biomass production across systems, with intensively managed systems being the most likely to benefit from climate change. Quantitative prediction of net effects of climate change on soil ecosystem services remains a challenge, in part due to knowledge gaps, but also due to the complex interactions between different aspects of climate change. Despite this challenge, it is critical to gain the information required to make such predictions as robust as possible given the fundamental role of soils in supporting human well‐being.